Risk assessment and molecular mechanism study of drug-drug interactions between rivaroxaban and tyrosine kinase inhibitors mediated by CYP2J2/3A4 and BCRP/P-gp - Zhao, Tingting; Li, Xuening; Chen, Yanwei; Du, Jie; Chen, Xiaodong; Wang, Dalong; Wang, Liyan; Zhao, Shan; Wang, Changyuan; Meng, Qiang; Sun, Huijun; Liu, Kexin; et al. (Frontiers in Pharmacology, 2022)
Cancer patients have a much higher risk of thrombotic diseases than common patients due to the abnormal hemodynamic profiles. While anticoagulant therapy always aggravated bleeding risks. Rivaroxaban was one of the most widely used direct oral anticoagulants (DOACs), which was applied for anticoagulant treatment or prophylaxis in clinic. The present study aimed to systemically estimate the combination safety of rivaroxaban with tyrosine kinase inhibitors (TKIs) based on human cytochrome P450 (CYPs) and efflux transporters, and explore the drug-drug interaction (DDI) mechanisms in vivo and in vitro. In vivo pharmacokinetic experiments, and in vitro enzyme incubation assays and bidirectional transport studies were conducted. Imatinib significantly increased rivaroxaban Cmax value by 90.43% (P<0.05) and AUC value by 119.96% (P<0.01) by inhibiting CYP2J2- and CYP3A4-mediated metabolism and breast cancer resistance protein (BCRP)- and P-glycoprotein (P-gp)- mediated efflux transportation in the absorption. In contrast, the combination of sunitinib with rivaroxaban reduced the exposure in vivo by 62.32% (P<0.05) and the Cmax value by 72.56% (P<0.05) through promoting BCRP efflux in the excretion. Additionally, gefitinib potently inhibited CYP2J2- and CYP3A4-mediated rivaroxaban metabolism with Ki values of 2.99 μΜ and 4.91 μΜ, however, it almost did not affect the pharmacokinetics of rivaroxaban in vivo. Taken together, clinically significant DDIs existed in the combinations of rivaroxaban with imatinib and sunitinib. Imatinib would increase the bleeding risks of rivaroxaban, while sunitinib had a risk of reducing therapy efficiency. Therefore, more attention should be paid to medication guidance of the combinations of rivaroxaban with TKIs.